Model Akad Hybrid (Murakkab) pada Fintech P2P Syariah di Indonesia: Analisis Kepatuhan Syariah dan Tantangan Regulasi 2025 - Ali, Haedir; Arsyad , Kamaruddin (Tangible Journal, 2025)
This study aims to examine and analyze the effect of the application of green accounting and environmental performance on profitability in food and beverage companies listed on the IDX in 2018-2022. Sampling was carried out by purposive sampling so that 08 companies were obtained. The type of data used in this study is secondary data obtained from the annual report of food and beverage companies listed on the IDX for 2018-2022. The analysis technique used in this study is by using regression analysis of panel data with the selected research model, namely the Random Effect Model (REM). The results of data research using Eviews (Econometric Views) version 12 conducted in this study shows that green accounting variables affect profitability because green accounting can be said to be a long-term investment of the company, because the funds spent today can provide a good name for the company. Environmental performance variables do not affect profitability, this is because even though the average company has obtained a blue rating, which means the company is making efforts for environmental management in accordance with the law. However, the results of environmental performance can be said to be unable to guarantee that the company's profitability will increase.